No evidence for interstitial lung oedema by extensive pulmonary function testing at 4,559 m - Dehnert, Christoph; Luks, Andrew M.; Schendler, Guido; Menold, Elmar; Berger, Marc Moritz; Mairbäurl, Heimo; Faoro, Vitalie; Bailey, D. M.; Castell, Christian; Hahn, G.; Vock, P.; Swenson, E. R.; et al. (The European respiratory journal, 2010)
The aim of the present study was to better understand previously reported changes in lung function at high altitude. Comprehensive pulmonary function testing utilising body plethysmography and assessment of changes in closing volume were carried out at sea level and repeatedly over 2 days at high altitude (4,559 m) in 34 mountaineers. In subjects without high-altitude pulmonary oedema (HAPE), there was no significant difference in total lung capacity, forced vital capacity, closing volume and lung compliance between low and high altitude, whereas lung diffusing capacity for carbon monoxide increased at high altitude. Bronchoconstriction at high altitude could be excluded as the cause of changes in closing volume because there was no difference in airway resistance and bronchodilator responsiveness to salbutamol. There were no significant differences in these parameters between mountaineers with and without acute mountain sickness. Mild alveolar oedema on radiographs in HAPE was associated only with minor decreases in forced vital capacity, diffusing capacity and lung compliance and minor increases in closing volume. Comprehensive lung function testing provided no evidence of interstitial pulmonary oedema in mountaineers without HAPE during the first 2 days at 4,559 m. Data obtained in mountaineers with early mild HAPE suggest that these methods may not be sensitive enough for the detection of interstitial pulmonary fluid accumulation.